Efficiency of essential oils in the control of the black bean aphid Aphis craccivora Koch (Hemiptera: Aphididae) - L. L. A. Bezerra; F. R. Azevedo; W. S. Evangelista-Júnior; F. J. Paula-Filho; D. M. A. F. Navarro; E. F. Santos (Brazilian Journal of Biology, 2023)
Abstract The black aphid Aphis craccivora Koch is one of the main pests of the caupi-bean crop Vigna unguiculata (L.) Walp. Due to the need to find effective and safe methods of control, there has been an increase in research seeking natural alternatives. Thus, the objective of this work was to evaluate the potential of essential oils from jatoba Hymenaea courbaril, copaiba Copaifera langsdorffii and aroeira Schinus terebinthifolius to control nymphs and adults of A. craccivora. The oils were extracted from the leaves by the hydrodistillation method, diluted to 0.1% in distilled water with 2% dimethyl sulfoxide (DMSO). Each treatment had four repetitions, plus a control with distilled water + 2% DMSO. The biotests were conducted in two stages: the first was conducted in the laboratory, under controlled conditions of temperature, relative humidity and photophase, and the second was conducted in the greenhouse, using only the treatment with the best laboratory test results. After 24, 48, 72, 96 and 120 hours of exposure, the insect mortalities were checked. In the first phase of the experiment, the aroeira oil showed 83.33% and 75.75% efficiency of mortality in nymphs and adults, respectively. In the greenhouse tests, this same oil showed 73.52% in nymphs and 62.85% in adults, opening new perspectives regarding its use as a natural insecticide for the control of the black aphid of the bean.